Inheritance and variability of productivity traits in hybrids of spring soft wheat of the first to fourth generations - L. V. Volkova (Аграрная наука Евро-Северо-Востока)
The effects of genotype-environment interaction of nine spring soft wheat varieties and seven hybrid populations F1 - F4 formed using these varieties were determined under the conditions of the Kirov region. The significant influence of environmental conditions on all studied traits was established. The contribution of the “year” factor to the number of grains per head in varieties and hybrids was 10.9 and 13.9%, respectively; to the mass of 1000 grains – 5.8 and 19.5%; to the yield – 47.3 and 41.1%. The genetic component made a significant contribution to the mass of 1000 grains in varieties and hybrids (81.5 and 58.8%), as well as to the number of grains in varieties (38.4%). There was a higher varietal specificity in the manifestation of traits in parental varieties compared to the hybrids. The analysis was done for two component traits of head productivity in a series of generations against the background of the action of various lim-factors, the shifts in their average values and the influence on yield were predicted and determined. The indicator of phenotypic domination (hp) in the first generation was determined according to the number of grains per head (hp = -5.00...+ 7.82) and 1000 grains mass (hp = + 0.23...+ 12.00), the combinations with a high level of heterosis were picked out (Baganskaya 95 x Novosibirskaya 44 and Baganskaya 95 x Aktjube 3). The calculation of the breeding differential and the effectiveness of the selections in contrasting environmental conditions of the second (2016) and third (2017) hybrid generations was carried out. Under the conditions of 2018, the yield of the initial populations varied within 219.0...789.6 g/m2, while the figures for the selected progenies were 317.0...647.6 g/m2. The average yield increase of the progenies that had been selected in the dry year was 56.8 g/m2 in relation to the initial populations (11.1%); the increase of the progenies, selected in the conditions of excess moisture was 10.8 g/m2 (3.0%). The correlation analysis revealed the average positive relationship between the first-generation hp indicator and the selection differential in subsequent generations according to the «1000 grains mass» (r = 0.18...0.63) and «number of grains per head» (r = 0.35...0.37) traits. The correlation was weak between the level of heterosis and the selection reaction (r = -0.12…0.27). The selection of genotypes with a high level of selection differential according to the number of grains per head was more effective than the selection according to the mass of 1000 grains. The correlation coefficient between the degree of phenotypic dominance of traits in the first generation and average values of traits in the F2-F4 generations varied within r = 0.35...0.68 (significant values at 5% level r = 0.75).